A New Application of Parallel Synthesis Strategy for Discovery of Amide-Linked Small Molecules as Potent Chondroprotective Agents in TNF-α-Stimulated Chondrocytes - Lee, Chia-Chung; Lo, Yang; Ho, Ling-Jun; Lai, Jenn-Haung; Lien, Shiu-Bii; Lin, Leou-Chyr; Chen, Chun-Liang; Chen, Tsung-Chih; Liu, Feng-Cheng; Huang, Hsu-Shan (PLOS ONE, 2016)
As part of an effort to profile potential therapeutics for the treatment of inflammation-related diseases, a diversity of amide-linked small molecules was synthesized by using parallel synthesis strategy. Moreover, these new compounds were also evaluated for their inhibitory effects on nitric oxide (NO) by using tumor necrosis factor alpha (TNF-α)-induced inflammatory responses in chondrocytes. Among the tested compounds, N-(3-chloro-4-fluorophenyl)-2-hydroxybenzamide (HS-Ck) was the most potent inhibitor of NO production and inducible nitric oxide synthase (iNOS) expression in TNF-α-stimulated chondrocytes. In addition, our biological results indicated that HS-Ck might suppress the expression levels of iNOS and matrix metalloproteinases-13 (MMP-13) activities through downregulating the activation of nuclear factor kappa B (NF-κB) and signal transducer and activator of transcription 3 (STAT-3) transcriptional factors. Therefore, the parallel synthesis was successful used to develop a new class of potential anti-inflammatory agents as chondroprotective candidates for the treatment of osteoarthritis.